2021
DOI: 10.1097/spv.0000000000001009
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Assessing the Impact of Opioid-Specific Patient Counseling on Opioid Consumption and Disposal After Reconstructive Pelvic Surgery

Abstract: Objectives This study aims to determine the effect of opioid-specific counseling on postdischarge opioid consumption and opioid storage/disposal patterns after reconstructive pelvic surgery. Methods In this multicenter randomized-controlled trial, participants were randomized to standard generalized counseling or opioid-specific perioperative counseling. Opioid-specific counseling was provided at the preoperative and 2-week postoperative visits with edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Proactive patient counseling has proven successful in other studies as well. For example, a 2021 study found in-hospital opioid counseling increased the disposal rate of unused opioids at 6 weeks post-surgery [ 20 ]. This reduces potential opioid misuse as there are fewer unused opioid pills in patients’ possession after surgery [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proactive patient counseling has proven successful in other studies as well. For example, a 2021 study found in-hospital opioid counseling increased the disposal rate of unused opioids at 6 weeks post-surgery [ 20 ]. This reduces potential opioid misuse as there are fewer unused opioid pills in patients’ possession after surgery [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 2021 study found in-hospital opioid counseling increased the disposal rate of unused opioids at 6 weeks post-surgery [ 20 ]. This reduces potential opioid misuse as there are fewer unused opioid pills in patients’ possession after surgery [ 20 ]. A 2020 study reported that the frequency of proper opioid disposal doubled after counseling, and that overall knowledge of opioid risks increased [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most first-time opioid abusers receive medication from a friend or relative with leftover medication, highlighting the importance of education for safe and proper disposal of unused narcotics. 10 , 11 , 21 The comment from a patient about the plan to keep pain medications in case they are needed in the future is a pivotal example of the need for continued re-education and safe handling of medications.…”
Section: Discussionmentioning
confidence: 99%
“… 9 However, interventions to reduce opioid diversion through patient education have a positive effect. 10 , 11 Institution-based Enhanced Recovery After Surgery (ERAS) opioid-prescribing recommendations also result in reduced opioid overprescribing. 12 However, adherence to ERAS protocols for opioid prescribing remains suboptimal.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 11 RCTs fulfilled the inclusion criteria, which comprised 1604 patients (804 received opioid education, while 800 received standard care). [10][11][12][13][14][17][18][19][20][21][22] Seven trials were conducted in orthopedic surgery, 2 in breast surgery, 1 in urogynecology, and 1 in obstetrical surgery (cesarean section). Five trials followed patients until 15 days after surgery, 6 trials reported information for 6 weeks after surgery, and 3 followed patients until 3 months (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%